2007
DOI: 10.1007/s10549-007-9672-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase-III trial of docetaxel/capecitabine versus doxorubicin/cyclophosphamide as primary chemotherapy for patients with stage II/III breast cancer

Abstract: We aimed to determine the efficacies of a non-anthracycline-containing regimen, docetaxel/capecitabine (TX), in comparison with an anthracycline-containing regimen, doxorubicin/cyclophosphamide (AC), as primary chemotherapy for node-positive early stage breast cancer. In this phase-III single center randomized study, we randomized 209 women with axillary node positive, stage II/III breast cancer to receive four cycles of either TX or AC followed by surgery and cross-over to the other treatment as an adjuvant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 27 publications
4
58
1
Order By: Relevance
“…The combined cancer drug used with either Docetaxel or Tamoxifen serve some clinical purposes, which include resistance management among patients, and enhancement of efficacy. Lee et al [13] found out that Capecitabine was more effective with Docetaxel in combined therapies (17% Pathological complete response (pCR)) among Hormone Receptor (HR)-positive breast cancer than combined therapy of doxorubicin and cyclophosphamide (3% pCR). In the combined therapy of TAM with VOR, VOR worked with TAM to manage hormone resistance among estrogen response (ER)-positive metastatic breast cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…The combined cancer drug used with either Docetaxel or Tamoxifen serve some clinical purposes, which include resistance management among patients, and enhancement of efficacy. Lee et al [13] found out that Capecitabine was more effective with Docetaxel in combined therapies (17% Pathological complete response (pCR)) among Hormone Receptor (HR)-positive breast cancer than combined therapy of doxorubicin and cyclophosphamide (3% pCR). In the combined therapy of TAM with VOR, VOR worked with TAM to manage hormone resistance among estrogen response (ER)-positive metastatic breast cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…(Tables 1-4 [9, provide an overview of trials involving capecitabine.) Combinations of capecitabine with standard chemotherapeutic regimens are still being actively investigated (Table 1 [9, [21][22][23][24][25][26][27] provides a summary of data from randomized clinical trials involving capecitabine with other chemotherapeutic agents) along with an increasing number of studies examining the use of capecitabine with newer targeted therapies ( …”
Section: Clinical Trials Involving Combination Therapy With Capecitabinementioning
confidence: 99%
“…Although evaluation of combinations of standard chemotherapeutic agents is continuing and wide ranging, with more than two dozen such trials ongoing [41], the present discussion reviews in detail only the completed pivotal trials for the established combination with docetaxel, together with some recent developments in taxane-based combination therapy. A list of other completed randomized trials evaluating capecitabine and chemotherapeutic agents in combination is presented in Table 1 [9, [21][22][23][24][25][26][27]. (For additional reviews of this topic, see O'Shaughnessy [2] and Fumoleau and Cameron [45].…”
Section: Established Combinations-taxane-based Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations